The The Utilization of Instagram by Wellner Consulting to Educate Tax Awareness - Maulia Dewanti, Dinda; Hariyati, Farida; Mustiawan, Mustiawan (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Tax is the main source of state revenue that plays an important role in supporting national development in various strategic sectors. Therefore, increasing tax awareness is the main focus of various institutions, including the Directorate General of Taxes (DGT) and other fiscal education actors. One of the approaches used in tax education is the utilization of social media, such as instagram, which has a wide reach and interactive features. This research aims to find out how Wellner Consulting utilizes the Instagram platform as a means of delivering tax education to the public. The research uses a descriptive qualitative approach with data collection methods through in-depth interviews and content analysis of the @wellnerconsulting Instagram account. In collecting and analyzing secondary data from Weliner Consulting's Instagram account, the author utilizes a digital tool called Reportei. The results showed that Wellner Consulting's digital communication strategy reflects the characteristics of convergent media, namely the incorporation of various content formats such as videos (Reels), images and text (carousels), and interactive features (Stories) in one platform. The strategy also involves two-way communication between the information provider and the audience, and is supported by data-driven evaluation to measure the effectiveness of the content. The findings show that tax information can be delivered in a light, interesting, and easy-to-understand manner, especially for the digital generation. Thus, Wellner Consulting's utilization of Instagram not only supports the dissemination of tax information, but also plays a role in shaping public tax awareness in a sustainable manner through an adaptive, communicative, and visual-based approach.